PEMANFAATAN HASIL SARI PATI JERUK GERGA UNTUK PENINGKATAN IMUNITAS TUBUH - Helvi Darsi; Endang Suswati; Erick Salman (LPPM Institut Pendidikan Nusantara Global, 2025)
The purpose of this community service is to provide education in the form of knowledge and skills to partners, namely the Gerga orange farmer group in Rimbo Pengadang District, Bengkulu Province, because agricultural products in the form of oranges are abundant in the area, which so far Gerga oranges have only been consumed without knowledge that if processed they can be one of the vitamins that can increase body immunity. The methods used are: 1) Socialization, 2) Training, 3) Application of technology, 4) Mentoring and evaluation, 5) Sustainability of the program. The results of this Community Service (a) laboratory tests of vitamin C content (8.80 Titrimetry), Potassium (61.68 Spectrophotometry), Sodium (8.88 Spectrophotometry), Fe (1.51 Spectrophotometry) and Sugar (11.00 Refractometry), (b) pretest and posttest results increased the quantity of Orange starch products by 0.68 in the medium category, (c) Increased packaging management capabilities by 2.92 in the effective category, (d) Marketing success by 49.52% in the quite effective category; (e) Increased knowledge by 3.93 in the good category, (f) Increased skills by 81.0% in the very good category. The output of community service activities is in the form of Sinta 4 journals, video IPR, poster IPR and online media.